An Investigation of a Nexus between Green Accounting Finance and Climate Risk: Fresh Insights from New Estimation - Trung, Nguyen Thanh (Journal of Environmental Accounting and Management, 2026)
This study explores the impact of green accounting financing (GAF) on climate risks (CR) across 34 European nations from 2005 to 2022. Employing advanced statistical techniques, our analysis confirms that GAF significantly mitigates environmental risks. This relationship persists even after accounting for variables such as democratization levels and trade shares, which may influence the GAF-CR dynamic in varied ways. Notably, the mitigative effects of GAF on CR are more pronounced over the long term. To validate these outcomes, the research utilizes multiple GAF indicators, illustrating that different types of GAF can effectively reduce CR, particularly under specific population state and economic conditions. The study further indicates that solid institutional frameworks within these European countries enhance the efficacy of GAF mechanisms in reducing climate risks.